Instrumental Technique, Expressivity, and Communication. A Qualitative Study on Learning Music in Individual and Collective Settings - Schiavio, Andrea; van der Schyff, Dylan; Biasutti, Michele; Moran, Nikki; Parncutt, Richard (Frontiers in Psychology, 2019)
In this paper we present a qualitative study comparing individual and collective music pedagogies from the point of view of the learner. In doing so, we discuss how the theoretical tools of Embodied Cognitive Science (ECS) can provide adequate resources to capture the main properties of both contexts. We begin by outlining the core principles of ECS, describing how it emerged in response to the information-processing approach to mind, which dominated the field for the latter half of the 20th century. We then consider the orientation offered by ECS and its relevance for music education. We do this by identifying overlapping principles between three tenets of ECS, and three aspects of pedagogical practice. This results in the categories of ‘instrumental technique’, ‘expressivity’ and ‘communication’, which we adopted to examine and categorize the data emerging from our study. In conclusion, we consider the results of our study in light of ECS, discussing what implications can emerge for concrete pedagogical practices in both individual and collective settings.